Cytosolic RNA binding of the mitochondrial TCA cycle enzyme malate dehydrogenase - Noble, Michelle; Chatterjee, Aindrila; Sekaran, Thileepan; Schwarzl, Thomas; Hentze, Matthias W. (RNA, 2024)
Several enzymes of intermediary metabolism have been identified to bind RNA in cells, with potential consequences for the bound RNAs and/or the enzyme. In this study, we investigate the RNA-binding activity of the mitochondrial enzyme malate dehydrogenase 2 (MDH2), which functions in the tricarboxylic acid (TCA) cycle and the malate-aspartate shuttle. We confirmed in cellulo RNA binding of MDH2 using orthogonal biochemical assays and performed enhanced cross-linking and immunoprecipitation (eCLIP) to identify the cellular RNAs associated with endogenous MDH2. Surprisingly, MDH2 preferentially binds cytosolic over mitochondrial RNAs, although the latter are abundant in the milieu of the mature protein. Subcellular fractionation followed by RNA-binding assays revealed that MDH2-RNA interactions occur predominantly outside of mitochondria. We also found that a cytosolically retained N-terminal deletion mutant of MDH2 is competent to bind RNA, indicating that mitochondrial targeting is dispensable for MDH2-RNA interactions. MDH2 RNA binding increased when cellular NAD+ levels (MDH2's cofactor) were pharmacologically diminished, suggesting that the metabolic state of cells affects RNA binding. Taken together, our data implicate an as yet unidentified function of MDH2-binding RNA in the cytosol.
Online verfügbar: 12. April 2024
Gesehen am 31.03.2025